The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/2177-6709.22.2.118-125.sar
|View full text |Cite
|
Sign up to set email alerts
|

Early vertical correction of the deep curve of Spee

Abstract: Even though few technological advancements have occurred in Orthodontics recently, the search for more efficient treatments continues. This paper analyses how to accelerate and improve one of the most arduous phases of orthodontic treatment, i.e., correction of the curve of Spee. The leveling of a deep curve of Spee can happen simultaneously with the alignment phase through a method called Early Vertical Correction (EVC). This technique uses two cantilevers affixed to the initial flexible archwire. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…15 To counteract this flaring, a rectangular archwire can be applied for leveling after the crowded teeth are aligned. 16 , 17 The amount of incisor intrusion should be introduced little by little to avoid any heavy force.…”
Section: Introductionmentioning
confidence: 99%
“…15 To counteract this flaring, a rectangular archwire can be applied for leveling after the crowded teeth are aligned. 16 , 17 The amount of incisor intrusion should be introduced little by little to avoid any heavy force.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to decrease the prolonged orthodontic procedure, it was suggested that auxiliary intrusion arches or cantilever springs are combined with resilient archwires during initial stage of treatment. 24 .…”
Section: Issn: 1110-435x Online Issn: 281-5258mentioning
confidence: 99%
“…Management of deepbite becomes more difficult with the existence of, or the increased severity of, an underlying skeletal discrepancy. Nonsurgical correction of a deep bite includes molar extrusion, incisor intrusion, or a combination of both, [3,4] with a general understanding that intrusion of teeth is more difficult than extrusion.…”
Section: Introductionmentioning
confidence: 99%